2011
DOI: 10.1143/jjap.50.01bg02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interface Nitride Layer on Electrical Characteristics of SiO2/Nitride/SiC Metal–Insulator–Semiconductor Diode

Abstract: Transport analysis during the transient phase of heating (a dynamic transport study) applied to the plasma with internal transport barriers (ITBs) in the Large Helical Device (LHD) heliotron and the JT-60U tokamak is described. In the dynamic transport study the time of transition from the L-mode plasma to the ITB plasma is clearly determined by the onset of flattening of the temperature profile in the core region and a spontaneous phase transition from a zero curvature ITB (hyperbolic tangent shaped ITB) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This indicated that the thickness of the nitridation layer was very small. The thickness of the surface layer can be estimated from XPS data [3]. Figure 3(b) shows the time dependence of the nitride thickness estimated from Si2p spectrum, together with the data of the samples prepared by the thermal nitridation in N 2 and NH 3 mixed gases reported by Sakai et.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This indicated that the thickness of the nitridation layer was very small. The thickness of the surface layer can be estimated from XPS data [3]. Figure 3(b) shows the time dependence of the nitride thickness estimated from Si2p spectrum, together with the data of the samples prepared by the thermal nitridation in N 2 and NH 3 mixed gases reported by Sakai et.…”
Section: Resultsmentioning
confidence: 93%
“…This indicated that the thickness of the nitridation layer was very small. The thickness of the surface layer can be estimated from XPS data [3].…”
Section: Resultsmentioning
confidence: 99%
“…The interface state density between the thin insulating layer and SiC was estimated from the current -voltage characteristics of MIS Schottky contact before and after the annealing [3,5], and are listed on Table I. The interface state density decreased after the annealing in the deposition chamber.…”
Section: Resultsmentioning
confidence: 99%
“…We have tried to use nitride layer as the insulating layer of SiC MIS devices [2,3,4]. It has been difficult to get the nitride layer thicker than several nm by direct nitridation method.…”
Section: Introductionmentioning
confidence: 99%
“…20,21,28 The origin of oxygen could be due to contamination in the furnace used for thermal nitridation or to oxygen incorporation from air exposure. Contamination in the furnace was minimized by pumping the system down to 10 À7 mbar prior to the introduction of 15 NH 3 gas, although the presence of oxygen during annealing cannot be ruled out, since the same furnace was previously used for thermal oxidations, and outdiffusion of O from its walls could occur during ammonia annealing.…”
mentioning
confidence: 99%